2013
DOI: 10.13172/2052-9287-1-2-681
|View full text |Cite
|
Sign up to set email alerts
|

Emission of radiation in the orthopaedic operation room: A comprehensive review

Abstract: Introduction Ionising radiation is a constant risk to exposed workers. Recently, it was shown that the incidence of malignant diseases was increased in an orthopaedic hospital among exposed personnel. However, the surgeons are often ill-informed about the utilisation of the fluoroscopic units, which leads to unnecessary exposure to radiation, for both the operating team as well as the patients. This review article aims to give a comprehensive review on the exposure of staff in the orthopaedic operation room an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…During an additional crosscheck of citations in Google scholar, one additional literature review was identified [1]. Finally, 34 publications matched the eligibility criteria (Table 3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During an additional crosscheck of citations in Google scholar, one additional literature review was identified [1]. Finally, 34 publications matched the eligibility criteria (Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…Only a few reviews reporting about radiation exposure of surgeons were found during the literature search [1,2,[32][33][34][35][36][37][38][39][40][41]. Of the 12 reviews, 4 were identified as appropriate.…”
Section: Systematic Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoroscopic procedures have been beneficial for patients undergoing orthopedic surgery because these minimally invasive procedures provide better direct visualization for soft tissue dissection, spare blood supply, and result in fewer complications than open surgeries [3,4]. However, during the fluoroscopic procedures, the surgeons may be exposed to the primary beam and scattered radiation [2,5]. As the use of fluoroscopy is continuously increasing in orthopedic surgery and orthopedic surgeons are often closely exposed to the radiation source during operations, they are considered a high-risk group of occupational radiation exposure [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Richter i wsp. wskazują, że odwracanie ramienia C pozwala na uzyskanie większej swobody ruchów operatora w polu operacyjnym [15]. Z doświadczenia autorki niniejszego listu jako audytora wewnętrznego wynika, że często takie ustawienie lampy rentgenowskiej jest stosowane przez lekarzy w celu geometrycznego powiększenia obrazu.…”
unclassified